Parliamentary army chaplains, 1642-51 - Laurence, A; Laurence, Anne (1982)
﻿ The intention of this thesis is to examine the careers of chaplains in the parliamentary armies and, more widely, the subject of religion in the parliamentary forces in the light of generalisations that have been made by historians about them. To this end, some 280 chaplains have been identified and their biographies have been summarised in the biographical index (Appendix II). The main text of the thesis, however, is devoted to a general discussion of chaplains' careers and of what has been said about them by seventeenth-century commentators and by later historians. The details of chaplains' employment, the circumstances of their service in the different parliamentary armies and their relationship with the clerical profession as a whole are assessed. In Chapter I consideration is given to the fact that most seventeenth-century commentators confined their remarks to either the armies of Essex and Manchester or the New Model army. Few said anything about service in the provincial forces, which, until l647, out-numbered the New Model army, or about the parliamentary forces which served in Ireland and Scotland. Hence this contemporary description cannot be considered to be representative of the majority of the parliamentary forces. Furthermore, much of the seventeenth-century writing on preaching in the parliamentary armies did not refer to chaplains. Thomas Edwards, for example, named many religious radicals who preached in the army of whom the majority were soldiers and junior officers, not chaplains. A number of the twentieth-century historians who have written on chaplains and religion in the parliamentary forces have not fully appreciated the limitations of some of the seventeenth-century writing on this subject. Particular attention is paid to the study by Professor Leo Solt of the political and religious ideas of certain New Model army chaplains. Dr. Mark Kishlansky's work on the New Model army is also discussed. It seems that twentieth-century historians have largely confined their observations to a few chaplains who served in the New Model army, especially those at the general's headquarters. These chaplains were singled out for comment by their contemporaries because they were unusual. The circumstances in which chaplains served are described in the second chapter, as well as the ways in which they were appointed and paid and what they did. It was considered normal for each regiment to have a chaplain, usually appointed by the colonel, sometimes with the advice of a body like the Westminster Assembly or a county committee (in the case of a provincial regiment). However, few regiments had chaplains continuously throughout their existence. It was difficult to recruit chaplains and few served for longer than a few months. Colonels seem to have appointed chaplains to keep up their troops' morale and to preach conformity to the beliefs of the army command. Colonels seem rarely to have appointed chaplains who shared their particular religious idiosyncracies. It is clear, however, that a number of chaplains shared a close personal and working relationship with their colonels, more so indeed than with one another, for there were rarely periods when large numbers of regiments were gathered together. Chaplains acted as messengers and confidential agents for their colonels, performing tasks which ranged from taking news of a victory to Parliament to helping to negotiate the marriage of Cromwell's son. The following five chapters are devoted to the chaplains in each of the main parliamentary armies: Essex's, Manchester's and Waller's, the provincial forces, the New Model, and the armies in Ireland and in Scotland. Most of the chaplains who joined the armies in the early months of the war were Presbyterians and several of them had been conspicuous for their opposition to the policies of Charles I and Archbishop Laud. As the war progressed the better known Presbyterians left, to return to their parishes or to sit in the Westminster Assembly. They were replaced by other Presbyterians and, increasingly, by Independents. However, the Independents in Manchester's army seem to have been conspicuous more because of their disputes with the Scottish Presbyterians in the same army than because of their numbers which were no greater than those in Essex's army. Dr. KisHansky contends, from Professor Solt's work, that only nine New Model army chaplains have been identified. However, over the period 1645-1658, thirty-eight men are known to have served as chaplains. The largest number serving simultaneously was seventeen (in l647), but even the smallest number was ten (in 1650). This suggests that by no means all regiments had chaplains. Nevertheless, regimental chaplains were not a negligible presence. The New Model army recruited a higher proportion of Independent chaplains than had served in the armies of Essex and Manchester, from which the New Model was largely recruited. This proportion continued to grow until 1647 when the Presbyterians were virtually driven out. The proportion of radical sectaries amongst the soldiers in the New Model remained small and the only sectarian chaplains seem to have been Baptists. It therefore seems unlikely that chaplains were responsible for influencing soldiers with radical political or religious ideas. Indeed, the extent to which they were identified with the army command by their appointments would have made this unlikely in any case. However, it seems probable that chaplains were partly responsible for making soldiers, dislocated from their normal environment, more receptive to new ideas. It is also likely that a number of chaplains were themselves influenced by these ideas, though they espoused them only after leaving the army. The provincial forces, until l647, outnumbered the other parliamentary forces and hence deserve more consideration than work on the parliamentary forces traditionally gives them. These forces were even more fragmented and short-lived than the others so it is hard to make generalisations about them. However, eighty-two men who served as chaplains in the provincial forces between 1642 and 1650 can be named. A high proportion of them were Presbyterian, and Presbyterians remained an important presence in the provincial forces longer than they did in the New Model. Sectaries seem to have been less tolerated than in the New Model and only one Baptist chaplain is recorded. Most of the provincial forces were recruited from and served in a confined area. They were officered by the local gentry and their chaplains were the local clergy, so they did not suffer the same dislocation as the soldiers in Essex's army and the New Model. They seem to have been markedly less receptive to radical political and religious ideas, possibly as a consequence of the retention of these local links. The armies which went to Ireland and Scotland were technically part of the New Model, but the army which went to Ireland seems to have been treated as an expeditionary force for which a number of people, particularly chaplains, were specially recruited. The chaplains who went to Ireland in 1649 and the early l65Os were expected to minister to the Protestant settlers as well as to the soldiers. It is, therefore, hard to distinguish precisely between those chaplains on the army establishment and those on the civil list. They were predominantly Independent, though several Baptists went too. Many of them seem to have had some previous connection with Ireland rather than any previous army experience. By contrast many of the chaplains who went to Scotland in 1650 were already serving in the army. The expedition to Scotland was seen more as an extension of the New Model's activities in England and Wales and most of those chaplains who went North in 1650 returned with the army in 1651. In the period 1642 to 1651, the Presbyterian chaplains in the parliamentary forces seem to have been replaced by Independents, though this process worked at a different pace in the individual armies. The Independents were never, however, supplanted by sectaries and of the sectaries only a few Baptists became chaplains. Chaplains do not, then, seem to have been responsible for sectarianism amongst the soldiers, nor did they encourage them to political radicalism. They may well have encouraged soldiers to be receptive to radical ideas, but only in those armies where the soldiers were already removed socially and geographically from their normal environment. Chaplains cannot, therefore, be seen as political commissars or ill-qualified opportunists. Most of them were men who had interrupted a normal clerical career to serve with the army.